Saprobic Dothideomycetes in Thailand: Neoaquastroma gen. nov. (Parabambusicolaceae) introduced based on morphological and molecular data - Wanasinghe, Dhanushka N.; Hyde, Kevin D.; Konta, Sirinapa; To-Anun, Chaiwat; Jones, E.b. Gareth (Phytotaxa, 2017)
In this paper we introduce Neoaquastroma, a novel genus from dead twigs, collected in northern Thailand. The genus is characterized by immersed, globose to subglobose or irregular-shaped ascomata, short papillate ostioles, a thin peridium, clavate asci with short pedicels, and multi-septate, hyaline ascospores with guttules in each cell. The morphological character differences and analyses of combined LSU, TEF, SSU and ITS sequence datasets, from a single ascospore isolate, support the validity of the new genus and its placement in Parabambusicolaceae. The new genus is compared with other genera in the family and a comprehensive description, and micrographs are provided.